Health Effects of Alternate-Day Fasting in Adults: A Systematic Review and Meta-Analysis - Cui, Yuanshan; Cai, Tong; Zhou, Zhongbao; Mu, Yingmei; Lu, Youyi; Gao, Zhenli; Wu, Jitao; Zhang, Yong (Frontiers in Nutrition, 2020)
Background: Alternate day fasting (ADF) method is becoming more and more popular among adults. The aim of this meta-analysis is to evaluate the effects of ADF for adults. Methods: Randomized controlled trials (RCTs) of ADF were searched using PubMed (1988 to Mar. 2020), EMBASE (1995 to Mar. 2020) and the Cochrane Controlled Trials Register. Systematic review was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-analyses. The datum was calculated by RevMan version 5.3.0. The original references of relating articles were also reviewed. Results: Seven RCTs involving 269 participants (152 in the ADF group and 117 in the control group) were studied. In this meta-analysis, compared with control group, ADF group showed statistically significant reductions in weight (p<0.00001) and body mass index (BMI) (p<0.00001). Besides, ADF group showed significant differences in terms of total cholesterol (TC) (p=0.001), low-density lipoprotein (LDL) (p=0.01), triglycerides (TG) (p=0.02), fat mass (p=0.002), lean mass (p=0.002), systolic blood pressure (SBP) (p=0.003), diastolic blood pressure (DBP) (p=0.007) and total calorie intake (p=0.007). At the same time, the analysis demonstrated that the ADF group had a same effect compared with control group in aspects of high-density lipoprotein (HDL) (p=0.27), homeostasis model assessment-insulin resistance (HOMA-IR) (p=0.55) and fasting blood sugar (FBS) (p=0.09). Conclusions: This meta-analysis suggests that ADF is a viable diet strategy for weight loss and it has a substantial improvement in risk indicators for diseases in obese or normal people.